The Behavior of Enlarged Base Pile Under Compression and Uplift Loading in Partially Saturated Sand - Ghalib, Zaid H.; Mahmood, Mahmood R. (Civil Engineering Journal, 2024)
The aim of this paper is to study the behavior of enlarged base piles embedded within partially saturated soils under compression and uplift loading. This type of pile is rarely excavated and cast on-site. Accordingly, to construct an enlarged base pile model, an excavator was designed and manufactured to give appropriate shape through drilling and casting in the laboratory through the design and manufacture of an excavator to produce piles with a shaft of 35 mm in diameter, 500 mm in length, and a base of 80 mm in diameter inclined at an angle of 60 degrees. Three different partial saturation soils were achieved by lowering the water level below the soil surface 20, 40, and 60 cm and measuring the suction force of each stage using a Tensiometer. The average matrix suction results were 6.4, 7.6, and 9.1 kPa for each lower water level, respectively. The test results showed that the bearing capacity of the enlarged base piles under compression load in partially saturated soil was higher than that in the case of full saturation because of matrix suction, with an improvement rate of 2.5–4.5 times compared with the case of fully saturated soil. Additionally, test results showed that the enlarged base piles subjected to uplift loading in partially saturated soil were significantly improved compared with the fully saturated condition, with an improvement rate of 1.5 - 3 times. The reason for this is the apparent surface cohesion of the sandy soil, which increases the bearing capacity of the sandy soil. This study sheds light on the phenomenon of apparent surface cohesion of sandy soil and the extent of its effect on increasing the soil’s resistance to the loads placed on it. Doi: 10.28991/CEJ-2024-010-10-08 Full Text: PDF